The Effect of Barista Service Quality on Guest Satisfaction at Hotel Neo Dipati Ukur Bandung - Melli Isliana; Susilawati Susilawati (An International Journal Tourism and Community Review, 2025)
This study aims to analyze the effect of barista service quality on guest satisfaction at the Neo Dipatiukur Hotel Bandung, a hotel café will be successful when a barista shows the best service to hotel guests, this attitude has a major influence on the success of a hotel in the field of hotel beverages. The research method that will be used is through interviews and observations. Participation in this study consisted of hotel guests, baristas, and related hotel industries. Data were collected through semi-structured interviews and analysis techniques. The focus of the study includes the values of barista service quality, such as the technical skills of a barista in mixing a drink and serving it, grooming which is intended as looking attractive and dressing politely, the whether a barista at the Neo bandung hotel has worked following the SOP (standard operational Procedure) in the Hotel, then the friendly attitude carried out by a barista by implementing 3 s namely (smile, greet, peace), as well as communication skills and propessionalism carried out. The results of the study showed that the quality of barista service had a significant effect on guest satisfaction. The implication of thisstudy is the importance training for baristas to ensure optimal service standards to improve guest experience at Hotel Neo Dipati Ukur Bandung.